Internalisasi Nilai-Nilai Tawadhu dalam Pembelajaran Pendidikan Agama Islam dan Implikasinya Sikap Moderat dalam Beragama Studi Kasus SMP N 3 Cepiring Kabupaten Kendal - Irdia Azidar (CV. Creative Tugu Pena, 2024)
This study aims to: (1) To find out the content of tawadhu' value in pai learning at SMPN 3 Cepiring Kab. Kendal.. (2) To know the internalization process of Tawadhu' value in PAI lessons at SMPN 3 Cepiring Kab. Kendal. (3) . To find out the impact of internalization of tawadhu value in PAI learning on moderation attitude in religion at SMPN 3 Cepiring Kab. Kendal. This type of research uses qualitative research, with the validity of observation data and triangulate data wherein the practice of research is crossed using interview guidelines. Based on the results of research that has been conducted at SMPN 3 Cepiring Kab. Kendal with the title